The significance of Nature for Philosophy of Technology - Perperidis, Giannis (Neusis, 2025)
This text explores the complex and evolving relationship between nature, humanity, and technology across three pivotal periods in the history of thought. The first section focuses on antiquity, particularly Aristotle, highlighting the ontological and teleological distinction between nature and artifice. In Aristotelian terms, nature possesses an intrinsic purpose, whereas technology is oriented toward an external end, rendering it a mimetic and, thus, subordinate domain. The second section turns to early modernity, where thinkers such as Francis Bacon and Thomas Hobbes articulate the rise of a dominant epistemic subject who, through the mathematization of nature, reduces it to a manipulable object of inquiry and control. In the contemporary digital era, nature is reconceived as a flow of data, and the human being is increasingly interpreted as one among many information-processing machines. Subsequently, the text presents alternative ontological approaches, such as Bernard Stiegler’s conception of the human as an inherently technical being, offering a critical counterpoint to anthropocentric and instrumental views of technology. Finally, Agostino Cera’s critique of the empirical turn in the philosophy of technology is introduced, along with his call for an ontological sensitivity in addressing technological phenomena. The overarching aim of the text is to argue that a robust philosophy of technology must be grounded in a philosophy of nature, without which it cannot adequately respond to the challenges of our contemporary technological condition.